Functional Play: Playfulness in User Interfaces - Soegiono, Orry Wijanarko (Auckland University of Technology, 2005)
The definition of a user interface varies, but in essence, a user interface stands between user and the content of a digital media. It can be seen as something that stands in the way and must be kept as transparent as possible. However, in this practical design project, the user interface is positioned to augment the experience of accessing the content, creating engagement to the content which is important, for the nature of user interfaces requires active participation and engagement from the user (Laurel, 1991). By drawing parallel with playful activities that have always been present in many aspects of life, this project posed this question: Can playfulness that compels many real life activities be incorporated into a digital user interface? Can the engagement of play implemented and becomes the engagement of a user interface? In answering these questions, the project looked to play as a social function, the psychology of engagement, established interactive user interfaces, and then they are explored further through abstract and functional experiment in interactivities and user interfaces, as an attempt to synthesize playfulness and user interface. The concept of playful interface also explores functionality as an important aspect of user interface. The explored specific context focuses on the user interface design for the web, although points that are raised can also be applied to other forms of interactive user interfaces. This project also involves evaluation methods that are relevant, involving both participatory and automatic user feedback, designed to evaluate the points argued. The concept is practically applied in the form of an interactive website, featuring playful interactive interfaces that provide access to the content, which is the concept of the project. The website provides feedback mechanisms that are used to evaluate the concept. The website is also open to public scrutiny, can be accessed by the general public. The Website can be accessed at http://www.fp.ac.nz
Keywords: User interfaces (Computer systems); Design; Play; Computer systems